Vibration of agglomerated CNTRC micro-scale beams carrying a moving concentrated load - Tran, Thi Thom; Nguyen, Dinh Kien (Vietnam Journal of Mechanics, 2024)
Vibration of micro-scale composite beams reinforced by carbon nanotubes (CNTRC beams) carrying a moving concentrated load is studied considering CNT agglomeration. The Eshelby-Mori-Tanaka method is adopted to predict the elastic moduli of the CNTRC. The modified couple stress theory and a refined high-order theory are employed to establish the mathematical model. The governing equation in terms of finite element analysis is established and solved by a direct integration method. The effects of the CNT reinforcement, the agglomeration of CNTs, the size scale parameter, and the load speed on the vibration of the beams are investigated in detail.